Financial support for the development of higher education in the field of physical culture and sports - Ksendzuk, Valentyna; Chyzh, Viktor (Public Policy and Accounting, 2024)
The article deals with the issue of financing education in the field of physical culture and sports in Ukraine. As part of this, the main indicators of the state budget of Ukraine in terms of financing the development of physical culture and sports were analyzed, which indicate the lack of growth dynamics of financial support in this area. This can be a demotivating factor for future specialists in physical culture and sports, because budgetary funding takes the lion’s share in financing the sector of physical education and sports. It is proposed to identify sports public organizations as one of the alternative entities that will act as an authorized customer for the training of specialists under educational programs in the field of physical culture and sports, it is proposed to consider. The introduction of budgetary/nonbudgetary financing of sports public organizations involves the creation of a system of subjects, principles and conditions of financing (legal obligations, economic justification, competitive principles in the form of the composition of the competitive commission and selection criteria). The improved approach allows taking into account the specific current needs of society and the effective use of available funding sources (budgetary or extra-budgetary). In turn, this contributes to the expansion of opportunities and gives new rights to public organizations that ensure the development of various types of sports. The proposed approach to the construction of a financial mechanism of state support for the development of higher education in the field of physical culture and sports allows to minimize the risks of the influence of external factors on educational activity and ensures compliance with such principles as: continuity, flexibility, correspondence of cost-result categories and efficiency, in the formation of state policy in the field of higher education, as well as the policy of higher education institutions.